Your move : a new approach to the study of movement and dance - Guest, Ann Hutchinson (Gordon and Breach, 1983)
Your Move: A New Approach to the Study of Movement and Dance establishes a fresh and original framework for looking at dance. In examining the basic elements of dance - the Alphabet of Movement - and using illustrations of movement technique and notation symbols it provides a new way to see, to teach and to choreograph dance. This book gives a list of primary actions upon which all physical activity is based, focusing on both the functional and expressive sides of movement.